APPRAISAL OF ATTITUDE IN ONLINE NEWSPAPER WRITTEN BY FEMALE AND MALE - Pramestika, Miraldha; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is entitled